The Reality of Law Enforcement in Indonesia in the Perspective of Law and Development: Should the Law be obeyed or feared? - Putri Edytya, Nindya; Satya Prawira, Reyhan (Lex Scientia Law Review, 2019)
Law and Development is a study related to the existence or validity of laws in the countries that are part of Development Studies. For Indonesian people, the existence of law depends on how the government enforces law in society. Therefore, it is necessary to bring law enforcement to be strict and authoritative in the Indonesian legal system in society. Based on this, the author's research uses a juridical-sociological research methodology that examines rules, concepts, and public views on law enforcement in Indonesia.